Outbreak of SARS-CoV-2 Cases during Omicron Variant Infections - Muhsin, Mohammed I.; Fadhil, Alaa H.; Hwaid, Asmaa Haseeb; Fadhil, Hula Y.; Aufi, Iman M.; Hamid, Nibras M. (Iraqi Journal of Science, 2024)
Despite the development of vaccines and a decrease in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infections cases, there is a constant concern about the occurrence of new waves during the coming winter, according to the World Health Organization. This study aimed to investigate the outbreak of the SARS-CoV-2 in patients with severe acute respiratory infections and influenza-like illnesses during Omicron variant infections in Iraq between January 2022 and August 2022. The real-time reverse transcription polymerase chain reaction (rRT-PCR), as the standard diagnostic protocol, was performed to analyze the nasopharyngeal swabs of 1879 people with acute respiratory and influenza-like illnesses. Of a total of 1879 participants, 520 (27.7%) showed confirmed infection with SARS-CoV-2 and the peak of infection was during winter season in January and February, and June during the summer season with a statistically significant difference. Males showed an 8% higher infection rate than females but without statistically significant differences. Among the positive cases 31-40, 21-30 and 41-50 age groups were the most affected with a highly statistically significant difference. The positive rate of infection was higher in Baghdad Governorate/Al-Rusafa district and Erbil Governorate with a highly statistically significant difference. The results of this study could help in monitoring the spread of the virus to put health professionals and officials in the Ministry of Health and the government to take precautionary measures to avoid the emergence of a new wave of disease in Iraq.